The potential and limitations of education in prison (Academic Journal of Internal Affairs, 2019)
This paper tries to give an understanding of education in Hungarian prisons and shows what motivates captives to learn. It offers a view both into opportunities and limits of the motivation.
Keywords: education; prison; motivation